Effectiveness of biologic treatment for psoriasis in Malaysia: Real-world evidence and review of current evidence from Southeast Asia - Zhenli Kwan; Sook Yee Michelle Voo; Wooi Chiang Tan; Jyh Jong Tang; Min Moon Tang; Wan Noor Hasbee Wan Abdullah; Latha R. Selvarajah; Ting Guan Ng; Rajalingam Ramalingam; Pubalan Muniandy; Winn Hui Han; Shin Shen Yong; et al. (Wolters Kluwer Medknow Publications, 2024)
Background Biological treatments are effective in the management of psoriasis. However, results in the real-world setting may differ from clinical trials. Objectives We aimed to evaluate the effectiveness of biological drugs among patients with psoriasis in Malaysia. Methods This was a retrospective review of adult patients on biologics who were notified to the Malaysian Psoriasis Registry between 2011 and 2019. Univariate and multivariate logistic regression was performed to identify factors associated with response to treatment in terms of the Psoriasis Area and Severity Index (PASI) 75, PASI 90, and Dermatology Life Quality Index (DLQI) 0/1. Results Of 130 patients, the most prescribed drug was ustekinumab (40.8%), followed by adalimumab (29.2%) and secukinumab (24.6%). Overall, the differences in the median PASI scores from baseline were −23.9 at 3-6 months, −25.8 at 12 months, and −27.8 at 3 years, while the difference in the median DLQI scores was −13.0 at 3-6 months. At 3-6 months, 57.6% achieved PASI-75, 32.9% achieved PASI-90, and 4.7% achieved PASI-100. These responses were sustained at 12 months and 3 years. Adalimumab was the most effective treatment with 88.9% achieving PASI-75, 77.8% PASI-90, and 22.2% PASI-100 at 3 years. However, secukinumab was more effective at achieving a PASI-100 response at 3-6 months (9.1%). Chinese or Indian ethnicity, concurrent use of systemic therapy or phototherapy, comorbidities, and a longer duration of psoriasis were associated with poorer response. Conclusion Biological treatments, particularly adalimumab and secukinumab, are effective in reducing disease severity and improving the quality of life of patients with psoriasis in Malaysia.